THE RELATIONSHIP CHARACTERISTIC AND KNOWLEDGE LEVEL MOTHERS' WITH ONE THOUSAND DAYS OF THE FIRST LIFE PRACTICE - Agustina Apriyani Yesenia; Regina Vidya Trias Novita (Journal of Maternity Care and Reproductive Health, 2022)
The incidence of stunting influenced various factors among others is not deliver information relating to nutrition during 1000 days the first of life. The knowledge and practices often is not reliable to implement complementary food during breastfeeding. The purpose of this study was to determine the relationship of the characteristics and level of knowledge of mothers with the practice of the first thousand days of life in the Watubaing health center in Sikka, Maumere, NTT. This research uses quantitative methods with cross sectional design. The research sample is mothers who have children one and a half to two and a half years old with a total sample of 124 respondents. Data collection tool in the form of a questionnaire about knowledge of complementary food during breastfeeding (MP-ASI)that has been tested for validity and reliability. Data analysis was performed using the Chi-Square test with a confidence level of a = 0,05. The conclusion of the study showed that the knowledge of mothers, that respondents in the category of knowledge enough with a percentage of 70,2%. There is a significant relationship between maternal education with the practice of the first thousand days of life that has (p value = 0,031), but there is no significant relationship between maternal age with the practice of the first thousand days of life that has (p value = 0,565), and knowledge of mothers with the first thousand days of life practice that has (p value = 0,072). Conclusion level of mother’s education influence how to giving nutrition for their child at 1000 days of life. The health education from health worker and cadre and companion the mother improve the capability to make, give and consume the healthy food for their babies. Keywords : Age, Education, Knowledge, Practice of the first thousand days of life.